1990
DOI: 10.1093/jnci/82.5.380
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoembryonic Antigen as a Selective Enhancer of Colorectal Cancer Metastasis

Abstract: Although the serum level of carcinoembryonic antigen (CEA) is directly associated with a poor prognosis in human colorectal carcinoma (CRC), its function is obscure. As a member of the immunoglobulin supergene family, CEA may be involved with intercellular recognition and binding and facilitate attachment of CRC to sites of metastasis. In an experimental metastasis model of CRC in athymic nude mice, a systemic injection of CEA enhanced experimental liver metastasis and implantation in liver by a weakly metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
93
0
4

Year Published

1993
1993
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(103 citation statements)
references
References 0 publications
5
93
0
4
Order By: Relevance
“…Increased CEA was found to be univariate adverse prognostic factor for survival in locally advanced or metastatic gastric cancer patients treated with first-line chemotherapy (Louvet et al, 2003). In our series, CEA 450 ng ml À1 was a negative prognostic factor and this may reflect the metastatic potential of malignant cells (Hostetter et al, 1990).…”
Section: Second-line Chemotherapy In Metastatic Gastric Cancer V Catasupporting
confidence: 47%
“…Increased CEA was found to be univariate adverse prognostic factor for survival in locally advanced or metastatic gastric cancer patients treated with first-line chemotherapy (Louvet et al, 2003). In our series, CEA 450 ng ml À1 was a negative prognostic factor and this may reflect the metastatic potential of malignant cells (Hostetter et al, 1990).…”
Section: Second-line Chemotherapy In Metastatic Gastric Cancer V Catasupporting
confidence: 47%
“…Because the precise involvement of this tumour marker in the development of liver metastases cannot be analysed in humans, many studies have been conducted using animal models to try to demonstrate a connection between cause and effect. Most of the studies designed to address this question were based on the hypothesis that the adhesive properties of CEA might facilitate the development of liver metastases from colorectal cancer (Hostetter et al, 1990;Jessup et al, 1993a;Tibbetts et al, 1993;Thomas et al, 1995;Landuzzi et al, 1996). Recently, some authors suggested that CEA could enhance liver metastases via induction of cytokines in Kupffer cells (Gangopadhyay et al, 1996;Edmiston et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…To analyse the involvement of circulating CEA on the development of liver metastases from colorectal carcinoma in nude mice, Jessup et al (1993a) and Hostetter et al (1990) injected CEA i.v. 30 min before i.s.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations